Prospective multicenter non-randomized controlled study on intraosseous stability and healing period for dental implants in the posterior region - Shinya Homma; Yasushi Makabe; Takuya Sakai; Kenzou Morinaga; Satoru Yokoue; Hirofumi Kido; Yasutomo Yajima (SpringerOpen, 2018)
Abstract Background A current implant body surface was treated with "rough processing" by sandblasting and acid etching for the purposes of obtaining more reliable osseointegration and shortening the treatment period. Various reports have examined the healing period with the use of these implant bodies, but a consensus opinion has not yet been obtained. The purpose of this study is to evaluate the relationship between insertion torque (IT) and implant stability quotient (ISQ) at implant treatment using the current rough-surfaced implant. We evaluated the implant treatment sites with ISQ values, IT values, and voxel values. Methods Participants in this study comprised 26 patients (10 males, 16 females; mean age, 55.5 years) who received posterior region dental implants at Tokyo Dental College Hospital or Fukuoka Dental College Hospital. For all participants, pretreatment computed tomography and determination of bone quality from voxel values were performed. Thirty-two implant bodies were inserted into the posterior region, and insertion torque was measured. ISQ was also measured at 0, 2, 4, 6, 8, and 12 weeks postoperatively. Results Eight implant bodies in the maxilla and 24 in the mandible were inserted. All ISQ values increased, exceeding 60 by 6 weeks postoperatively. For insertion torque < 30 N cm, ISQ increased significantly after 8 weeks. For ≥ 30 N cm, the ratio at which high ISQ values appeared increased significantly after 6 weeks. Compared with the treatment area with insertion torque < 40 N cm, the treatment area ≥ 40 N cm showed a significantly higher voxel value. Conclusions No significant relationship was found between the insertion torque value and the ISQ value. Also, it was suggested that the ISQ value was considered to be an important indicator for observing the treatment state of the implant.